THE INFLUENCE OF PAPER BAGS ON THE ORGANOLEPTIC AND QUALITY PARAMETERS OF APPLE JUICE - Dilnoza Ganieva (Modern American Journals, 2025)
Pre-harvest fruit bagging is a horticultural practice used to improve the external quality of apples, but its effects on the internal attributes essential for juice production are complex. This study was conducted to evaluate the influence of different colored paper bags on the quantitative and organoleptic parameters of juice from ‘Starcrimson’ and ‘Mutsu’ apple cultivars.
Keywords: Apple, fruits, paper bags, white paper bag, yellow paper bag, black paper bag, fruit juice yield, juice clarity, juice taste rating, overall quality rating.